Inovasi Teknologi Wearable dalam Monitoring Glukosa pada Diabetes Mellitus Tipe 2 : Literatur Review - Badu, Franning Deisi; Suriani, Sari; Ibrahim, Sri Zeineke; Djafar, Lisa; Salamena, Dian Hariani; Indar, Indar (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Type 2 Diabetes Mellitus (T2DM) is a global health challenge with prevalence continuing to increase. Management of this condition relies heavily on accurate and continuous monitoring of blood glucose levels. Wearable technology has emerged as an innovative solution that offers convenience, comfort, and accuracy in glucose monitoring. This article is a literature review that aims to analyze the role of wearable technology in monitoring glucose in T2DM patients, including its effectiveness, limitations and development prospects.Research shows that wearable devices, such as Continuous Glucose Monitoring (CGM), have the advantage of providing real-time data, increasing patient engagement in self-management, and supporting better clinical decision making. However, several challenges remain, including affordability, accuracy under certain conditions, and user acceptance of this technology. In addition, connectivity with other digital tools, such as smartphone applications and cloud-based platforms, enables more comprehensive data integration to support holistic management. This review concludes that wearable technology has great potential in transforming the management of T2DM, particularly in encouraging data-driven approaches and personalization of care. To maximize its benefits, more research is needed on long-term efficacy, technological improvements, and strategies to increase accessibility.